KESENIAN TRADISIONAL DI ERA KOMODIFIKASI BUDAYA: PERGESERAN MAKNA MAGIS-RELIGIUS DALAM KESENIAN JARANAN - M. Syahrul Ulum (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2020)
Through tourism, especially cultural tourism, cultural dynamics turmoil also occurs in tourist destinations. This is be cause there is an inevitable tug-of-war between culture on the one hand and tourism on the other hand. Cultural traditions represent the expression of tradition and tourism represents modernity (economy).In general, cultural traditions have a tendency to preserve and tourism as the industry wants to maximize its business activities for profit. This research is more focused on the study of cultural practices which a focus on the discussion of Roland Barthes’s semiotics on the traditional art of jaranan. The results of this study can be concluded that Barthes’s semiotic analysis of the commodification of culture in jaranan art experiences a variety of forms and dance offerings that be conceptualized as profit-making. The concept of withdrawal is very clearly seen by the shift in religious magical meanings from sacred to profane in every performance.